Methylaluminoxane (MAO)-Assisted Direct Amidation of Esters - Desrat, Sandy; Ducousso, Aline; Gapil, Shelly; Remeur, Camille; Roussi, Fanny (Synlett, 2015)
Aliphatic and aromatic esters are efficiently transformed into amides in good to excellent yields, under mild conditions using methylaluminoxane (MAO). This reaction can be performed either at room temperature or by applying microwave irradiation.
Keywords: amidation; MAO; esters; amides; microwave